Heritage Conservation in Indonesia: Policy Review - Lubis, Lunariana; Wardiyanto, Bintoro; Setijaningrum, Erna (Perspektif Hukum, 2024)
The Indonesian government has handed over its authority to ministries and local governments in the field of culture in the designation of cultural heritage since 2010. However, protection of cultural heritage remains limited due to unclear policies and planning. This study aims to identify gaps in existing cultural heritage conservation policy and planning and propose a revised policy framework. After reviewing the cultural heritage conservation policy framework in Indonesia, several shortcomings were found that affect the cultural heritage conservation process. These deficiencies include insufficient coverage of heritage’s context, insufficient institutional capacity, a heritage-owner approach to conservation, inadequate incentives, lack of funding sources, and lack of transparency. To address these shortcomings, several new policies are recommended, including revision of the political system, provision of integrated conservation approaches and incentives, diversification of funding sources, and expansion of public participation.